Antihypertensive Amaranth Protein Hydrolysates Encapsulation in Alginate/Pectin Beads: Influence on Bioactive Properties upon In Vitro Digestion - Dora Elisa Cruz-Casas; Rodolfo Ramos-González; Lilia Arely Prado-Barragán; Cristóbal N. Aguilar; Raúl Rodríguez-Herrera; Anna Iliná; Sandra Cecilia Esparza-González; Adriana Carolina Flores-Gallegos (Polysaccharides)
Protein hydrolysates containing bioactive peptides have emerged as therapeutic agents. However, these peptides may lose this bioactivity under gastrointestinal conditions. Encapsulation in edible biopolymers is a solution to this problem. Protein hydrolysates with ACE-I inhibitory activity, obtained previously, were encapsulated. A 1% solution of the biopolymers alginate (AG) and pectin (PC) in various ratios was prepared. The beads formed were evaluated in both wet and dry states for size, roundness, thermal gravimetric analysis (TGA), encapsulation efficiency, and ACE-I inhibitory activity. Selected samples underwent in vitro digestion, after which peptide release and ACE-I inhibitory activity were determined. Size analysis revealed that increasing the PC content increased the bead size, with 100% PC beads showing total deformation and reduced roundness. TGA indicated that wet beads had lower thermal stability compared to dry beads. The highest encapsulation efficiency (95.57% ± 0.49) was observed with 100% AG beads. The 75% AG 25% PC beads exhibited the highest ACE-I inhibitory activity (97.97% ± 1.01). Encapsulated protein hydrolysates retained their ACE-I inhibitory activity after simulated digestion, whereas non-encapsulated hydrolysates lost their bioactivity. Encapsulation of amaranth protein hydrolysates with AG and PC thus preserves antihypertensive activity even after in vitro digestion.